Islamic Education Curriculum in Junior High Schools - Muhamad Nursyahid; Dety Mulyanti (Riviera Publishing, 2024)
The Islamic education curriculum in Junior High Schools (SMP) plays an important role in shaping students' character and spiritual values. This research aims to analyze the curriculum structure, teaching methods, and challenges in implementing the Islamic education curriculum in junior high schools. The research methodology used is qualitative with a case study approach in several junior high schools in Indonesia. Data was collected through interviews, observation and document analysis. The research results show that the Islamic education curriculum in junior high schools includes subjects such as the Al-Qur'an, Hadith, Fiqh, Aqidah, Akhlak, and the History of Islamic Culture. The teaching methods applied vary, from lectures, discussions, to religious practices. The main challenges faced are limited resources, teacher readiness, and support from the school and parents.